Bribery in Government Agency: A Phenomenological Study - Eka Wirajuang Daurrohmah; Dekar Urumsah (Universitas Pendidikan Ganesha, 2021)
The bribery case in Indonesia has always been sticking out all the time. In the last ten years, bribery has always been the most cases handled by the KPK. This phenomenon often sticks out, and the lack of research on the detection of bribery has attracted researchers to research and explore the detection of bribery in government agencies. This study used a qualitative method with a phenomenological approach and data analysis assisted by the Nvivo software. Based on the results of this research, every people have the right to detect bribery, but this right is limited, and not all have the ability. The perpetrators of bribery can come from internal and external organizations. There is a stimulant for the perpetrator to commit bribery which is also stated in the fraud pentagon theory. The results of this study are expected to contribute to auditors in conducting forensic audits and investigations and organizations in making policies related to anti-fraud policies. It is hoped that future research can expand the research construct on the detection of bribery.